Appreciating the Fear of Conflict and the Possibilities in Disagreement. (19th July 2021) - Furlong, Mark; Brophy, Lisa
Abstract: The present contribution seeks to strengthen the capacity of social workers to respond to the experience of potential or actual conflict. In this project, an initial stage involved scanning the available literature. This process yielded two general findings: (i) most of the available literature is specialist in nature and (ii) the available social work literature concentrates on conflicts between workers and clients. The second stage in the exercise develops a set of linguistic distinctions, for example that disagreement can be distinguished from confrontation. Building on this set, three vignettes are examined as concrete sites in which formulations of, and responses to, conflict are developed. An outline of symmetrical and complementary processes is then introduced. This theoretical material is central at the consideration of a final, more complex vignette—an engagement that consolidates, and then extends, the themes developed earlier in the paper. A general proposition is raised: deliberately engaging with the issue of conflict offers opportunities for personal and professional growth. More specifically, it is suggested that those who tend to avoid conflict can usefully experiment with leaning into, rather than away from, disagreement whilst those who tend towards directness can usefully practice behaviours that engage with difference more obliquely. Abstract : Loud voices, threats, intimidation and actual violence—these are the images many of us associate with the term 'conflict'. This is all scary stuff, but disagreements do not always have to be disagreeable and differences do not have to be destructive. Sometimes, trying to avoid conflict escalates tensions. This paper seeks to de-mystify the term 'conflict' and to offer a series of vignettes that adult learners will find accessible and constructive. Why is this important? If one is working for change it is rare that everything proceeds smoothly. It follows that finding ways to engage with difference, with disagreement, is what progressive social workers have to be able to do. This provocative paper is about becoming more conflict capable.